Diagnostic accuracy of handheld dynamometry and 1-repetition-maximum tests for identifying meaningful quadriceps strength asymmetries - Sinacore, J. A.; Evans, A. M.; Lynch, B. N.; Joreitz, R. E.; Irrgang, J. J.; Lynch, A. D. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Study Design: Clinical measurement, cross-sectional. Background: Quadriceps deficits are common in individuals with knee joint impairments and impact functional and quality-of-life outcomes. Quadriceps strength symmetry influences clinical decisions after knee injury. Isometric electromechanical dynamometry (ISO-ED) is the gold standard for measuring symmetry, but is not available in all clinical settings. Objectives: To compare concurrent validity of handheld dynamometry and 1-repetition-maximum leg press, knee extension from 90° to 0°, and knee extension from 90° to 45° to that of ISO-ED in identifying meaningful quadriceps strength deficits. Methods: Fifty-six participants with knee joint impairments completed ISO-ED and 4 alternative measures of quadriceps strength symmetry in a single session. Absolute agreement of alternative measures with ISO-ED was calculated with intraclass correlation coefficients (ICCs). Clinical agreement values at thresholds of 80% and 90% symmetry were compared between the alternatives and ISO-ED. Results: Knee extension from 90° to 45° (ICC = 0.67) and handheld dynamometry (ICC = 0.70) had the greatest ICCs. Clinical agreement was also best for these measures for 80% symmetry (k = 0.56 and 0.55, respectively) and 90% symmetry (k = 0.19 and 0.33, respectively). Conclusion: Handheld dynamometry and 1-repetition-maximum testing of knee extension from 90° to 45° are fair alternatives, although symmetry is typically overestimated. Receiver operating characteristic analysis identified alternative measure thresholds that correlated with the 80% and 90% symmetry thresholds on the ISO-ED. Clinicians should use more stringent symmetry values for these alternative tests to increase the probability that individuals have a minimum ISO-ED symmetry of 80% or 90%.